Analysis of Hospitals' Perceptions of the Implementation of Blockchain Technology in Medical Data Management - Nathaniel, Adriel; Wijaya, Bayu Angga; Gurusinga, Andre Apriandi; Gultom, Yoan Pahrul; Sianturi, Eldo Jan Parulian (Program Studi Pendidikan Teknologi Infromasi UMK, 2026)
Medical data management in hospitals requires a system capable of maintaining the security, integrity, and confidentiality of patient data due to the high risk of leakage, input errors, and difficulties in exchanging information between hospitals. Blockchain technology is one of the innovations that has the potential to improve the security and transparency of medical data management. This research focuses on analyzing the perception of hospitals on the benefits of implementing blockchain technology in medical data management. The approach applied in this study is quantitative descriptive with a pre-test and post-test scheme through the distribution of questionnaires to health workers and related staff. The data were processed using descriptive statistical methods to identify changes in perception before and after providing an understanding of blockchain technology. The results showed an increase in the average perception of respondents from 3.07 to 4.18, indicating an increase in understanding and acceptance of the technology. In general, this study shows that blockchain technology has the potential to improve security, transparency, efficiency, and implementation readiness in the management of medical data in hospitals.